1997
DOI: 10.1111/j.1365-2249.1997.259-ce1139.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of T cells in bronchoalveolar lavage fluid (BALF) and peripheral blood of patients with diffuse panbronchiolitis; the importance of cytotoxic T cells

Abstract: SUMMARYWe investigated the contribution of T cells in diffuse panbronchiolitis (DPB) by identifying T cell subsets in BALF of 36 patients with DPB, before and after long-term treatment with macrolide antibiotics, and 16 healthy control subjects. The percentages of lymphocytes and CD3þ gd þ cells in BALF of DPB patients and control subjects were similar, but the absolute number of these cells was higher in DPB patients. Treatment resulted in a significant reduction in the absolute number of these cells. A furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…In addition, a significant increase in the percentage and absolute number of activated cytotoxic (CD8+, HLA-DR+, CD11b+) cells has been observed [54,55]. The number of CD4+ cells is also increased, with a predominance of CD4+CD29+ memory T-cells [53].…”
Section: Pathogenesismentioning
confidence: 96%
“…In addition, a significant increase in the percentage and absolute number of activated cytotoxic (CD8+, HLA-DR+, CD11b+) cells has been observed [54,55]. The number of CD4+ cells is also increased, with a predominance of CD4+CD29+ memory T-cells [53].…”
Section: Pathogenesismentioning
confidence: 96%
“…ϩ CD11b Ϫ cytotoxic T cells in BAL fluid from subjects with DPB (131). Macrolide suppression of proinflammatory cytokine production may be the principal mechanism of action in DPB (71, 183,283).…”
Section: Dpbmentioning
confidence: 99%
“…We previously reported that long-term MCL treatment reduced the number of lymphocytes in bronchoalveolar lavage fluid (BALF) of patients with DPB [12,13]. In this regard, elimination of lymphocytes by apoptosis is important in the control of chronic pulmonary inflammation [14].…”
Section: Introductionmentioning
confidence: 99%